"A LEAP 2 conclusions? Targeting the ghrelin system to treat obesity and diabetes" - Deepali Gupta; Sean B. Ogden; Kripa Shankar; Salil Varshney; Jeffrey M. Zigman (Elsevier, 2021)
Background: The hormone ghrelin stimulates food intake, promotes adiposity, increases body weight, and elevates blood glucose. Consequently, alterations in plasma ghrelin levels and the functioning of other components of the broader ghrelin system have been proposed as potential contributors to obesity and diabetes. Furthermore, targeting the ghrelin system has been proposed as a novel therapeutic strategy for obesity and diabetes. Scope of review: The current review focuses on the potential for targeting ghrelin and other proteins comprising the ghrelin system as a treatment for obesity and diabetes. The main components of the ghrelin system are introduced. Data supporting a role for the endogenous ghrelin system in the development of obesity and diabetes along with data that seemingly refute such a role are outlined. An argument for further research into the development of ghrelin system-targeted therapeutic agents is delineated. Also, an evidence-based discussion of potential factors and contexts that might influence the efficacy of this class of therapeutics is provided. Major conclusions: It would not be a "leap to" conclusions to suggest that agents which target the ghrelin system - including those that lower acyl-ghrelin levels, raise LEAP2 levels, block GHSR activity, and/or raise desacyl-ghrelin signaling - could represent efficacious novel treatments for obesity and diabetes.